2023
DOI: 10.1002/anie.202305298
|View full text |Cite
|
Sign up to set email alerts
|

Design Rules for Two‐Dimensional Organic Semiconductor‐Incorporated Perovskites (OSiP) Gleaned from Thousands of Simulated Structures**

Abstract: Two‐dimensional (2D) halide perovskites are an attractive class of hybrid perovskites that have additional optoelectronic tunability due to their accommodation of relatively large organic ligands. Nevertheless, contemporary ligand design depends on either expensive trial‐and‐error testing of whether a ligand can be integrated within the lattice or conservative heuristics that unduly limit the scope of ligand chemistries. Here, the structural determinants of stable ligand incorporation within Ruddlesden‐Popper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Synthesizing a conjugated ligand is a demanding process that usually requires several steps and isolation procedures to obtain products with high purity. Besides the work of predicting 2D perovskites using ML models reported by Lyu et al and Lin et al, , it is of interest to extend the current chemical scope with diverse structural combinations and scrutinize the structure–property relationships between ligands and the resulting 2D and quasi-2D perovskites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Synthesizing a conjugated ligand is a demanding process that usually requires several steps and isolation procedures to obtain products with high purity. Besides the work of predicting 2D perovskites using ML models reported by Lyu et al and Lin et al, , it is of interest to extend the current chemical scope with diverse structural combinations and scrutinize the structure–property relationships between ligands and the resulting 2D and quasi-2D perovskites.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several ML models have been successfully trained to accelerate the finding of new 3D halide perovskites. Deep learning models, classical ML models, as well as a high-throughput screening frameworks have been developed to predict various electronic properties and aid ligand design with well-discovered features. Lin et al recently published a molecular dynamics (MD) simulation study of over 10k prospective OSiPs to establish design rules for stable ligand incorporation (Figure d) . Due to the ability of the ligands to relax across unit cells, they found that ligands larger than the unit cell along one dimension can still be accommodated in many cases and that linker selection plays a critical role for several specific body chemistries.…”
Section: Structure and Properties Of Osipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dou and co-workers recently performed a molecular dynamics (MD) study of over ten thousand simulated 2D HOIP structures, including an algorithmically generated set of prospective cation chemistries and all previously reported experimental primary ammonium cations based on C, H, O, S, and N, with the goal to obtain the structural determinants of organic cation incorporation and 2D HOIP stability. 76 In terms of molecular design, they found that the overall stability trend of a 2D HOIP for a given cation is more strongly constrained by the molecular structure of the organic core than by the side-chains substituted onto that core or by the structure of the spacer between the core and the ammonium group. Organic cores composed of combinations of larger repeating units result in 2D HOIP structures with a lower average structural stability.…”
Section: Challengesmentioning
confidence: 99%